Предмет: Алгебра,
автор: Гулима1
Помогите решить дальше
Приложения:
Ответы
Автор ответа:
0
9ˣ+6ˣ=2²ˣ⁺¹
3²ˣ+3ˣ*2ˣ-2*2²ˣ=0
Пусть 3ˣ=t>0 2ˣ=v>0 ⇒
t²+tv-2v²=0
t₁,₂=(-v+/-√(v²-4*(-2v²))/2=(-v+/-√(v²-(-8v²))/2=(-v+/-√(v²+8v²))/2=
=(-v+/-√(9v²))/2=(-v+/-3v)/2.
t₁=(-v+3v)/2=2v/2=v
t₂=(-v-3v)/2=-4v/2=-2v ∉, так как t>0, v>0 ⇒
t=v
3ˣ=2ˣ |÷2ˣ
3ˣ/2ˣ=1
(1,5)ˣ=1
x=0.
Ответ: x=0.
3²ˣ+3ˣ*2ˣ-2*2²ˣ=0
Пусть 3ˣ=t>0 2ˣ=v>0 ⇒
t²+tv-2v²=0
t₁,₂=(-v+/-√(v²-4*(-2v²))/2=(-v+/-√(v²-(-8v²))/2=(-v+/-√(v²+8v²))/2=
=(-v+/-√(9v²))/2=(-v+/-3v)/2.
t₁=(-v+3v)/2=2v/2=v
t₂=(-v-3v)/2=-4v/2=-2v ∉, так как t>0, v>0 ⇒
t=v
3ˣ=2ˣ |÷2ˣ
3ˣ/2ˣ=1
(1,5)ˣ=1
x=0.
Ответ: x=0.
Похожие вопросы
Предмет: Русский язык,
автор: aoaoaoaoaoa5
Предмет: Қазақ тiлi,
автор: nysanklovasirinkul
Предмет: Алгебра,
автор: mamajonovmuxtorjon5
Предмет: Математика,
автор: abek2004198
Предмет: Литература,
автор: pino2005